Fusidic acid cream in the treatment of impetigo in general practice: double blind randomised placebo controlled trial - Koning, Sander (BMJ, 2002)
OBJECTIVE: To test the hypothesis that fusidic acid would not increase the treatment effect of disinfecting with povidone-iodine alone in children with impetigo. DESIGN: Randomised placebo controlled trial. SETTING: General practices in Greater Rotterdam. PARTICIPANTS: 184 children aged 0-12 years with impetigo. MAIN OUTCOME MEASURES: Clinical cure and bacterial cure after one week. RESULTS: After one week of treatment 55% of the patients in the fusidic acid group were clinically cured compared with 13% in the placebo group (odds ratio 12.6, 95% confidence interval 5.0 to 31.5, number needed to treat 2.3). After two weeks and four weeks the differences in cure rates between the two groups had become smaller. More children in the placebo group were non-compliant (12 v 5) and received extra antibiotic treatment (11 v 3), and more children in the placebo group reported adverse effects (19 v 7). Staphylococcus aureus was found in 96% of the positive cultures; no strains were resistant to fusidic acid. CONCLUSIONS: Fusidic acid is much more effective than placebo (when both are given in combination with povidone-iodine shampoo) in the treatment of impetigo. Because of the low rate of cure and high rate of adverse events in the placebo group, the value of povidone-iodine in impetigo can be questioned.